Great big beautiful life [compact disc, unabridged] - Henry, Emily (Reese's book club., 2025)
Alice Scott and Hayden Anderson are both on balmy Little Crescent Island to write the biography of a woman no one has seen in years, or at least to meet with the octogenarian who claims to be the Margaret Ives. Tragic heiress, former tabloid princess, and daughter of one of the most storied (and scandalous) families of the twentieth century. The problem is, Margaret is only giving each of them pieces of her story. Pieces they can't swap to put together because of an ironclad NDA and an inconvenient yearning pulsing between them every time they're in the same room.